2003
DOI: 10.1002/bjs.4017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of perianal abscess and fistula-in-ano in children

Abstract: Drain, don't probe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 5 publications
1
28
1
2
Order By: Relevance
“…Traditionally, surgical management of perianal abscess and fistula-in-ano has been the accepted treatment [7,8,12,14,15]. Incision and drainage is the most common procedure used for perianal abscess, and fistulotomy or fistulectomy, which has no difference in the recurrence rate [7,14] although few reports advocated the fistulectomy [15,16], has been the popular surgical treatment of fistula-in-ano. However, recent studies have shown that conservative treatment is a good alternative for these diseases [1,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, surgical management of perianal abscess and fistula-in-ano has been the accepted treatment [7,8,12,14,15]. Incision and drainage is the most common procedure used for perianal abscess, and fistulotomy or fistulectomy, which has no difference in the recurrence rate [7,14] although few reports advocated the fistulectomy [15,16], has been the popular surgical treatment of fistula-in-ano. However, recent studies have shown that conservative treatment is a good alternative for these diseases [1,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…1 Some cases were treated by needle aspiration of the abscess. 17 The most accepted approach is incision and drainage of the abscess 4,6,8,14,[17][18][19]21 under local anesthesia. 1,8,22 A more radical approach, using incision with simultaneous fistulotomy and cryptotomy under general anesthesia, has been found to reduce significantly the recurrence or FIA rate.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment has historically been with fistulotomy when the fistula is found or incision and drainage without identification of the fistula [4]. Some authors have advocated diligent search for the fistulous tract [5] while others believe that excessive probing may result in iatrogenic fistula formation [4]. Recently, some investigators have suggested that conservative management of PAAs results in a lower fistula rate than with operative intervention [6].…”
Section: Introductionmentioning
confidence: 98%
“…Children with FIA typically have few serious sequelae. Treatment has historically been with fistulotomy when the fistula is found or incision and drainage without identification of the fistula [4]. Some authors have advocated diligent search for the fistulous tract [5] while others believe that excessive probing may result in iatrogenic fistula formation [4].…”
Section: Introductionmentioning
confidence: 99%